Legal Compliance of the Acehnese Tamiang Community with Provisions for Divorce Pledges Before the Court (A Sociological Study of Islamic Law) - Fuad, Zahlul (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
This study aims to determine the practice and perceptions of the people of Aceh Tamiang about the legal provisions of divorce vows using a sociological approach to Islamic law. This research is a field study using a qualitative approach. The place of implementation of this research is in Aceh Tamiang District. The research data comes from primary data, namely data obtained from the field by means of observation and interviews. The results of the study show that the practice of divorce vows that developed in the Aceh Tamiang community was found to be inconsistent with the provisions of applicable state law. There are still many cases of divorce outside the Sya'iyah Court by directly declaring divorce to his wife without going through the trial process. The public's perception of the practice of divorce in court is only for administrative needs, has nothing to do with the validity of the law, and does not produce a solution or way out for married couples who want to separate, it is even more troublesome for the community with the cumulative issue of costs and the trial process is so long, that the community reluctant to deal with the court. As a result of the public's lack of understanding about the benefits of divorce in court, favorable laws regarding divorce in Indonesia have been neglected. Because of this, it is necessary to socialize the law and understand the negative effects of out-of-court divorce on the community. Furthermore, it is suggested that the government carry out legal harmonization between Islamic law that is developing in the community and the current divorce law rules. The pledge of talak (divorce) outside the court should be considered valid, as long as it fulfills all the conditions and pillars of Islam and its truth can be proven in court. For the sake of achieving benefits and guaranteeing legal certainty, presumably, a divorce that the husband has handed down outside the court must be reported to the Religious Court/Syar'iyah Court as validation of the divorce.